The stress response of intensive care unit medical doctors facing repeated severe emergencies - Ciuffini, Roberta; Marrelli, Alfonso; Leuter, Cinzia; Stratta, Paolo; Paladini, Antonella; Ciccozzi, Alessandra; Marsili, Ida; Marinangeli, Franco; Piroli, Alba (Frontiers in Psychology, 2022)
Objectives This study assesses the psychopathological distress experienced by doctors working in an Intensive Care Unit (ICU) during the COVID-19 pandemic. These doctors were the same who faced the consequences of a previous natural disaster, a severe 6.3 magnitude earthquake. A second objective is to evaluate their current mental attitude, professional performances and coping strategies adopted in the pandemic in relation to the conditioning effect of that first emergency, the earthquake. Methods Thirty-seven ICU medical doctors were recruited and assessed using Rapid Stress Assessment (RSA) rating scale, Symptom Checklist-90 Revised (SCL-90-R), Zung Self-Rating Anxiety Scale, Beck Depression Inventory, Beck Hopelessness Scale, Millon Clinical Multiaxial Inventory III. Comparison between exposure to the earthquake and Covid pandemic has been made in terms of professional role and psychological burden. Results Comparison between 2009 earthquake catastrophe and Covid pandemic conditions evidenced relevant changes in professional role, team, environment, shifts and work organization. Conclusions The doctors, who already experienced the 2009 earthquake reported a feeling of greater insecurity facing this latter catastrophe, the Covid pandemic, as well as perception of greater concern for their family and the global situation. However, having participated in the medical management of another emergency (the 2009 earthquake) appears to have contributed to limiting demoralization and psychological distress. The feeling of having greater decision-making possibilities and participation in the organization of work, strengthen coping skills in the face of the emergency